2014
DOI: 10.1007/978-3-319-05401-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Politics Matters: Dynamics of Inter-organizational Networks among Immigrant Associations

Abstract: Abstract. We model the dynamics of the two-mode network among directors and boards of voluntary associations, using a stochastic actorbased model, SIENA [12], including the structural effects proposed in [6], and considering the political orientation of associations as a covariate. Using data from [14], we compare the evolution of interlocks among Turkish associations in two European capitals, and explain the noticeable difference in structure by looking at statistically significant differences among the estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…In sociological studies, interest may lie in the evolution of web communities, group memberships and Facebook-like forum participation, employment preferences, scientific collaboration (Holme et al, 2007;Kang et al, 2007;Leydesdorff & Schank, 2008;Memon & Wiil, 2013;Opsahl, 2013;Snijders et al, 2013). In political studies, examples of twomode longitudinal networks are found in the analysis of the dynamics of people's affiliation to organizations and their participation in political events (Faust et al, 2002;Gagliolo et al, 2014). Examples of multi-modal and multi-relational networks are also found in the marketing research when considering the market basket analysis where customers buy, rent, or rate products (Horvat & Zweig, 2012) or in biological studies where diseases and genes are linked with respect to the different criteria (Davis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In sociological studies, interest may lie in the evolution of web communities, group memberships and Facebook-like forum participation, employment preferences, scientific collaboration (Holme et al, 2007;Kang et al, 2007;Leydesdorff & Schank, 2008;Memon & Wiil, 2013;Opsahl, 2013;Snijders et al, 2013). In political studies, examples of twomode longitudinal networks are found in the analysis of the dynamics of people's affiliation to organizations and their participation in political events (Faust et al, 2002;Gagliolo et al, 2014). Examples of multi-modal and multi-relational networks are also found in the marketing research when considering the market basket analysis where customers buy, rent, or rate products (Horvat & Zweig, 2012) or in biological studies where diseases and genes are linked with respect to the different criteria (Davis et al, 2011).…”
Section: Introductionmentioning
confidence: 99%